TECHNOLOGICAL INNOVATIONS AND STRUCTURAL TRANSFORMATION IN AFRICAN ECONOMIES (International Journal of Innovative Technologies in Economy, 2022)
This paper examines the role of technological innovations on structural transformation on economies of Africa. To attain this objective, it uses a sample of 32 African countries. The estimation techniques are system GMM and two stage least Square. Results indicate that technological innovations, as measured by total patents applications, have a significant effect on per sector value added. This result supports the almost nonlinear relationship of structural transformation since this study shows that manufacturing is the dominant sector in the promotion of structural changes as far as the implementation of technological innovations is concerned. Also, our results highlight that with regards to the African context, manufacturing is the sector in which technological innovation has the greatest impact on per sector value added and by so doing, it promotes structural transformation than other sectors (services or agriculture sector). As policy implication, governments need to encourage technological infrastructure through private and public spending on research and development especially for agricultural development to foster structural transformation.